2015
DOI: 10.1039/c5pp00145e
|View full text |Cite
|
Sign up to set email alerts
|

Inverted methoxypyridinium phthalocyanines for PDI of pathogenic bacteria

Abstract: Phthalocyanines (Pc) are photoactive molecules that can absorb and emit light in a large range of the UV-Vis spectrum with recognized potential for medical applications. Considering the biomedical applications an important limitation of these compounds is their low solubility in water. The use of suitable pyridinium groups on Pc is a good strategy to solve this drawback and to make them more effective to photoinactivate Gram-negative bacteria via a photodynamic inactivation (PDI) approach. Herein, an easy synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Tetra‐cationic thio‐pyridinium ZnPcs were able to cause a 5.0 log of reduction on the viability of a recombinant bioluminescent strain of E. coli . Similarly, inverted tetra‐ and octa‐methoxypyridinium ZnPcs showed 4.1 log of bioluminescence emission reduction against the same recombinant bioluminescent strain of E. coli and under similar PDI conditions . Tri‐ and tetra‐cationic pyridyloxy In(III)Pc cause reductions of ∼8.5 log in E. coli .…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tetra‐cationic thio‐pyridinium ZnPcs were able to cause a 5.0 log of reduction on the viability of a recombinant bioluminescent strain of E. coli . Similarly, inverted tetra‐ and octa‐methoxypyridinium ZnPcs showed 4.1 log of bioluminescence emission reduction against the same recombinant bioluminescent strain of E. coli and under similar PDI conditions . Tri‐ and tetra‐cationic pyridyloxy In(III)Pc cause reductions of ∼8.5 log in E. coli .…”
Section: Introductionsupporting
confidence: 93%
“…688 nm along with a broad shoulder peak until ca . 840 nm probably due to the presence of aggregates . In addition, ZnPc 2 shows the Q‐band slightly redshifted in comparison to ZnPc 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature have shown that cationic charges of PSs are more effective [21][22][23]. In addition, this accumulation occurs faster in microbial cells and could selectively bind to these microorganisms while PS accumulation is slow in normal mammalian cells [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained with macrocycles such as porphyrins, (Alves et al 2015), phthalocyanines (Dei et al 2006, Pereira et al 2012, Ryskova et al 2013, Lourenço et al 2015, Marciel et al 2017 or porphycenes (Xavier et al 2010, RuizGonzález et al 2015, Masiera et al 2017) are particularly relevant. The discovery that positively charged PS at physiological pH values promote the photoinactivation of microbial cells, namely of antibiotic resistant Gram-negative bacteria has stimulated the development of new useful cationic PS for PDI.…”
mentioning
confidence: 99%
“…(Lim et al 2012, Hwang et al 2012, Agadjanian et al 2009, Cardote et al 2012, Iglesias et al 2015, Barata et al 2013, Preuß et al 2014, Pohl et al 2014. According to that and following our interest in the development of tetrapyrrolic macrocycles with antibacterial activity, (Alves et al 2009, 2014b, Carvalho et al 2009, Costa et al 2012, Pereira et al 2012, Gomes et al 2013, Mesquita et al 2014a, b, Simões et al 2016, Lourenço et al 2015, Rocha et al 2015, Batalha et al 2015, Moura et al 2016, Castro et al 2017 we decided to synthesize the cationic corrole derivatives 2b and 3b and to study, for the first time, their efficiency in the PDI of Gram-negative bacteria. Herein, the synthesis, structural characterisation, photophysical properties (absorbance and singlet oxygen generation) and biological activity of the new cationic corroles against the naturally bioluminescent bacterium Allivibrio fischeri (A. fischeri) will be reported.…”
mentioning
confidence: 99%